Boosting Nitrate Electroreduction to Ammonia on Alloying of Cu With Au by Accelerated Proton Relay - Shuchun Sun; Deliang Zhang; Dongrun Li; Chuncheng Xu; Hongyu Mou; Lei Feng; Shuhua Lv; Caixia Song; Jibin Song; Debao Wang (Aggregate)
ABSTRACT Bimetallic nanoparticles (NPs) are recognized as effective catalysts for the nitrate reduction reaction (NO3–RR) to produce ammonia (NH3) due to their multiple active sites and electron redistribution enabled by strong metal–metal interactions. An in‐depth analysis of the reaction mechanism is essential for advancing efficient electrocatalysts. In this study, carbon‐supported Au3Cu alloy catalysts (Au3Cu/CC) were synthesized and applied for the direct reduction of NO3− to NH3. The NH3 generation rate achieved with Au3Cu/CC was 1719.3 µg h−1 cm−2, and the Faraday efficiency (FE) of NH3 was measured at 95.1% under an ultra‐low potential of −0.5 V versus RHE. The high activity of Au3Cu/CC is attributed to the synergistic interactions between Au and Cu sites in relay catalysis, where Cu exhibits selective activity in the reduction of NO3− to *NO, while Au demonstrates excellent performance in the subsequent reduction of *NO to NH3. Additionally, strong d–d orbital hybridization adjusts the d–band center of the alloy NPs, effectively modulating the adsorption energies of NO3− and *N to facilitate the direct reduction of NO3− to NH3. This synergistic electrocatalytic approach offers a novel strategy for designing efficient and multifunctional NO3−RR catalysts.